Annual cool-season forage systems for fall grazing by cattle - Villalobos, Luis Alonso, author; Brummer, Joe E., advisor; Davis, Jessica G., committee member; Whittier, Jack C., committee member; Meiman, Paul, committee member (Colorado State University. Libraries, 2015)
Extending the grazing season is one method that beef producers can use to reduce the need for preserved forages and supplements as these are the major inputs influencing profitability of their operations. Annual forages planted during mid- to late-summer have great potential for extending the grazing season into the fall and early winter in northern Colorado and similar environments. The development of forage systems for livestock operations must start with selection of forage species/cultivars that can yield enough biomass and have a high enough nutritive value to meet the requirements of the livestock to be fed. Accordingly, the research in this dissertation started with an evaluation of nine forage brassica cultivars from which four were chosen based on their unique traits. Barnapoli rape (Brassica napus L. var. napus) had the highest yields and stood up under a snow load; Groundhog radish (Raphanus sativus var.oleifer Strokes) and Barkant turnip (Brassicas rapa L. var. rapa) had fast growth and their bulbs provided extra feed and penetrated the soil, potentially reducing compaction; and Pasja hybrid (Chinese cabbage [Brassica rapa L. chinensis] x Turnip hybrid) had a high leaf-to-stem ratio which provided high quality forage for beef cattle. These were combined in a four-way mixture and evaluated in subsequent studies. In addition, the above study evaluated the impact of planting date on resulting yields of the brassicas and determined that they need to be planted by mid- to late-July to yield high amounts of biomass that can be stockpiled for fall grazing. The nutritive value of the brassicas was high and did not decline over time, but they were very low in fiber which can create rumen upset for beef cattle grazing them in monocultures or in brassica only mixtures. To develop a more balanced diet for beef cattle, the brassica mixture was seeded with cool-season grasses (triticale [×Triticosecale Wittm ex A. Camus {Secale x Triticum}], winter wheat [Triticum aestivum L.], and barley [Hordeum vulgare L.]) following a warm-season hay crop (pearl millet [Pennisetum glaucum L.]) that was either controlled or allowed to regrow. When the latter was controlled by spraying, brassicas dominated the mixtures to the detriment of the cool-season grasses which contributed little to available dry matter. The seed proportions of the cool-season grasses within the mixture were much lower than those used when grown in monocultures. When the proportions of cool-season grasses within mixtures were increased, their contribution to yield increased. Oats (Avena sativa) were particularly competitive when grown with the brassica mix. When the millet was allowed to regrow, it dominated the available dry matter, which influenced overall yield and nutritive value of the mixtures. Mixtures of cool-season forages and millet regrowth had lower quality than the same mixtures grown where the millet was controlled. This resulted from the brassicas dominating the mixtures where the millet regrowth was controlled, which resulted in higher quality that will likely require fiber supplements for grazing cattle. Mixtures grown with millet had higher fiber content, which negates the need for fiber supplementation. Cool-season forages and mixtures were also interseeded into corn at the V6 growth stage, which resulted in higher quality biomass on offer to beef cattle grazing cornstalks during fall and winter months. Their higher quality negates the need for supplementation, especially of protein, that is usually required to offset the low nutritive value of cornstalks. Of the forages evaluated, the brassica mix and annual ryegrass (Lolium perenne L. ssp. multiflorum [Lam.] Husnot) had the highest yields which was the determining factor for interseeded cool-season forages to compete with the costs of preserved forages that are normally used as supplements for beef cattle grazing cornstalks. Thus, the forage systems described in this dissertation provide insight into how annual forages can extend the grazing season into the fall and early-winter months, reducing the need for preserved forages to be fed in beef cattle operations. Sustainability of production systems can be enhanced when producers integrate current knowledge into their operations. Planting annual forages has the potential to benefit production of livestock and crops.
Keywords: annual crops; beef cattle; cool-season; cover crops; forages; grass